Knowledge‐based systems: A re‐evaluation - Abdullah, Mohd Syazwan; Kimble, Chris; Benest, Ian; Paige, Richard (Emerald Group Publishing Limited, 2006)
Purpose – The goal of this paper is to re-evaluate the role of knowledge-based systems (KBS) in knowledge management (KM). While knowledge-based systems and expert systems were widely used in the past, they have now fallen from favor and are largely ignored in the knowledge management literature.This paper aims to argue that several factors have changed and it is now time to re-evaluate the contribution that such systems can make to knowledge management. Design/methodology/approach – The role of KBS in KM is explored through a comprehensive analysis of both the management and the technical literature on knowledge. The literature on KBS and expert systems is reviewed and some of the problems faced by them are highlighted.Some of the probable causes of these problems and some of the solutions that might be used to overcome them are indicated.The paper describes how knowledge systems (KS) could be used as an effective tool for managing knowledge.Findings – The lack of success of KBS technologies for managing knowledge is mainly due to organizational and managerial issues.These problems can be solved through feasibility studies before system development activities. KS technology is now being successfully applied in a variety of newer domains that exploit its capabilities. Practical implications – Some conclusions are drawn concerning integration of knowledge systems with knowledge management, problems of the early implementation of knowledge systems technology, and possible solution to overcome these problems. Originality/value – The main contribution of the article is in re-evaluating the role of knowledge-based systems as a tool for knowledge management.